Open chest and pericardium facilitate transpulmonary passage of venous air emboli. Issue 5 (4th March 2021) - Storm, Benjamin S.; Halvorsen, Per Steinar; Skulstad, Helge; Dybwik, Knut; Schjalm, Camilla; Christiansen, Dorte; Wisløff‐Aase, Kristin; Fosse, Erik; Braaten, Tonje; Nielsen, Erik W.; Mollnes, Tom E.
Abstract: Background: Transpulmonary passage of air emboli can lead to fatal brain‐ and myocardial infarctions. We studied whether pigs with open chest and pericardium had a greater transpulmonary passage of venous air emboli than pigs with closed thorax. Methods: We allocated pigs with verified closed foramen ovale to venous air infusion with either open chest with sternotomy and opening of the pleura and pericardium (n = 8) or closed thorax (n = 16). All pigs received a five‐hour intravenous infusion of ambient air, starting at 4‐6 mL/kg/h and increased by 2 mL/kg/h each hour. We assessed transpulmonary air passage by transesophageal M‐mode echocardiography and present the results as median with inter‐quartile range (IQR). Results: Transpulmonary air passage occurred in all pigs with open chest and pericardium and in nine pigs with closed thorax (56%). Compared to pigs with closed thorax, pigs with open chest and pericardium had a shorter to air passage (10 minutes (5‐16) vs. 120 minutes (44‐212), P  < .0001), a smaller volume of infused air at the time of transpulmonary passage (12 mL (10‐23) vs.170 mL (107‐494), P  < .0001), shorter time to death (122 minutes (48‐185) vs 263 minutes (248‐300, P  = .0005) and a smaller volume of infused air at the time of death (264 mL (53‐466) vs 727 mL (564‐968), P  = .001). In pigs with open chest and, infused air and time to death correlated strongly ( r  = 0.95, P  = .001). Conclusion: Open chest and pericardium facilitated the transpulmonary passage of intravenously infused air in pigs.